How to Evaluate GDP-Linked Warrants : Price and Repayment Capacity - Miyajima, Ken (IMF Working Papers; Working Paper ;, 2006)
Following a brief review of the recent history of GDP-linked instruments, this paper proposes a set of tools to examine the quantitative properties of GDP-linked warrants. It argues that trigger conditions should be clearly identifiable and payment amounts easily calculable. Based on a design that includes these features and historical data for the main EMBI countries, the paper provides an assessment of the issuer's capacity to service GDP-linked warrants, comparing payments with tax revenues stemming from contemporaneous growth. The price of the GDP-linked warrants are then estimated from the point of view of both domestic and foreign investors.